UNCOVERING THE KEY DETERMINANTS SHAPING ELECTRIC VEHICLES ADOPTION IN INDONESIA - Ang Amelia; Keni Keni (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Fossil fuel-powered vehicles are among the major causes of Green House Gas (GHG) output, with Indonesia ranking in the top ten globally. The transition to Electric Vehicles (EVs) in Indonesia is progressing at a modest pace. To support EVs adoption and its environmental benefits, this analysis aims to understand predictors of EVs buying behavior. A survey targeting people domiciled in Jabodetabek, who use EVs or want to purchase EVs, was conducted via questionnaires. Subsequently, Partial Least Square Structural Equation Modeling was employed. On a 5-point Likert scale, 121 respondents were collected. The outcomes showed that price value, subjective norms, perceived ease of use and attitude can predict purchase intention positively and significantly. Furthermore, price value, perceived usefulness and perceived ease of use can predict attitude positively and significantly. Meanwhile, perceived usefulness and perceived behavioral control can’t predict purchase intention significantly. Attitude fully mediates the relationship between perceived usefulness and purchase intention, also partially mediates the relationship between price value and purchase intention and perceived ease of use and purchase intention. These findings imply that emphasizing value, usability, and social influence can strengthen attitudes and purchase intention toward EVs. By identifying key behavioral and technological determinants of EV adoption, this study offers empirical insights for policymakers in supporting environmentally sustainable transportation in Indonesia.